History of the Kaili Ethnic Petambuli Tradition in Kayumalue Ngapa Village - Idil, Idil; Juraid, Juraid; Suyuti, Suyuti; Hasan, Hasan; Nongtji, Minarni; Jayanti, Ika Nur (Journal of English Language and Education, 2025)
This study aims to examine the development, implementation, and symbolic meanings of the Petambuli customary practice within the wedding tradition of the Kaili ethnic community in Kayumalue Ngapa, Palu City. Employing a qualitative research approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that the Petambuli tradition has undergone notable transformations over time, particularly in the use of ritual instruments, traditional attire, and the customary dialogues performed during the ceremony. Despite these changes, the core values and philosophical essence of the tradition remain preserved. Petambuli is regarded as a sacred procession symbolizing respect and the readiness of the groom before entering the bride’s family home. Moreover, ritual objects such as the doke, tinggora, buya kae lapa, and dulang carry symbolic meanings that represent perseverance, courage, harmony, and ceremonial completeness. Overall, the Petambuli tradition plays a vital role in sustaining the cultural heritage of the Kaili community.